2019
DOI: 10.3390/met9050550
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hot-Mounting on the Microstructure of an As-Quenched Auto-Tempered Low-Carbon Martensitic Steel

Abstract: The effect of hot-mounting for metallographic studies of as-quenched low-carbon martensitic steels has been studied. Hot-mounting is typically carried out at 150–200 °C, i.e., a low-temperature tempering regime. Cold- and hot-mounted specimens from an as-quenched low-carbon auto-tempered steel were examined using a scanning electron microscope and their hardness levels were also compared. It was found that hot-mounting causes additional tempering that manifests as the appearance of new precipitates in those re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Due to the high M s temperature, the formation of martensite was followed by the precipitation of carbides. The precipitates have been previously identified as cementite [2]. This observation is also consistent with the observations of Speich [15], where only cementite precipitates form in quenched martensite with a carbon content <0.2 wt.%.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Due to the high M s temperature, the formation of martensite was followed by the precipitation of carbides. The precipitates have been previously identified as cementite [2]. This observation is also consistent with the observations of Speich [15], where only cementite precipitates form in quenched martensite with a carbon content <0.2 wt.%.…”
Section: Resultssupporting
confidence: 91%
“…This study has shown that the custom image processing program was able to qualitatively estimate and compare the volume fractions of the auto-tempered carbides formed in as-quenched low carbon steels. To demonstrate how the image processing tool can be utilized in practice, a steel sample with the same chemical composition as that above was austenized and water-quenched at 1000 • C/s in a similar way to that described in [2]. The SEM micrograph of the resulting microstructure is shown in Figure 8a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations